(untitled) (Fountain Journal of Natural and Applied Sciences, 2018)
Maize crop (Zea Mays), also known as corn, is the most widely cultivated plant and popular cereal grains in Nigeria that had found its usage in every home either as food for human beings or feed for animals, and importantly, raw material for food processing industries. It grows across a range of agro-ecological zones in Nigeria. The incidence of crop pest had been one of the major challenges faced by the farmers, resulting in low yield of crop production, both in quality and quantity. Another major challenge is that majority of farmers lack key knowledge in identifying plant diseases. Awkwardly, such knowledge typically resides within a few experts and is not easily accessible to farmers. Farmers initially necessitate to useful advices for diagnosing the various pests and diseases confronting the crops, before being able to implement a suitable treatment or control measures. To make this knowledge more widely available, a rule-based Expert System (ES) was designed and implemented in this paper. The ES comprises of a diagnosis system that detects pest in maize plant; an information system that gives facts about maize and pests, with their control measures; and finally an expert advice on maize plant cultivation. To make the system more user-friendly, an image database was integrated with it. The system was developed using HTML, CSS, JavaScript, PHP and Bootstrap. The application can supply information on 17 pests that affect maize plant in Nigeria, and their respective treatments. Keywords: Agriculture, Crops, Expert Systems, Pests control, Plant diseases, Maize..